On the Timelessness of Music Dictionaries - Bergenholtz, Henning; Bergenholtz, Inger (Lexikos, 2007)
Abstract: A music dictionary for the Internet fulfils the same functions as printed music dictionaries. An earlier music dictionary is as useful as a new one if its information is correct. But the fact that an Internet dictionary can at any time be corrected according to modern practices makes it, if not timeless, at least more up to date. Furthermore, the possibilities of illustrating with picture and sound open a wide field of usefulness. Nevertheless the lexicographer has to be aware of the different needs of different user types in different user situations. The dictionary being discussed, Musikordbogen, has been designed for text reception rather than translation or text production. After the inception of the dictionary has been described, the way the possibilities of the Internet has influenced the concept and the content of the articles and the outer texts is discussed.